2014
DOI: 10.1016/j.sjopt.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Partial HELLP syndrome with unilateral exudative retinal detachment treated conservatively

Abstract: Peripartum vision loss, an uncommon, often reversible complication of pregnancy usually occurs in the setting of pre-eclampsia or eclampsia. The HELLP syndrome is characterized by hypertension, elevated liver enzymes and low platelets. This is a rare case of unilateral exudative retinal detachment associated with the Partial HELLP syndrome that occurred after delivery in a 23-year-old Indian woman. The retinal detachment subsequently reattached with good visual improvement under conservative treatment. This ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Recientemente, otros autores han mencionado que en la isquemia por vasoconstricción coroidea se produciría una fuga de agentes vasoconstrictores, tales como la angiotensina II, adrenalina y vasopresina desde la coriocapilar al líquido intersticial coroideo; agentes que está comprobado se producen en pacientes con PE 13 . La fisiopatología del DR exudativo en PE no es del todo conocida, aunque la isquemia coroidea pudiera jugar el papel fundamental en esta entidad 14 . Figura 4.…”
Section: Discussionunclassified
“…Recientemente, otros autores han mencionado que en la isquemia por vasoconstricción coroidea se produciría una fuga de agentes vasoconstrictores, tales como la angiotensina II, adrenalina y vasopresina desde la coriocapilar al líquido intersticial coroideo; agentes que está comprobado se producen en pacientes con PE 13 . La fisiopatología del DR exudativo en PE no es del todo conocida, aunque la isquemia coroidea pudiera jugar el papel fundamental en esta entidad 14 . Figura 4.…”
Section: Discussionunclassified
“…HELLP syndrome is a complication of pregnancy characterized by three criteria: hemolysis, elevated liver enzymes, and low platelet count. Partial HELLP syndrome (pHELLP) is defined by the presence of one or two features of HELLP syndrome but not the complete form [2][3][4]. There are no reliable data on its incidence [3].…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature, we identified 43 case reports and case series documenting serous retinal detachment during pregnancy. Our review included 97 women diagnosed with preeclampsia with a median gestational age at presentation of 31.9 weeks (range 20–40 weeks) [ 5 , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. Of cases with blood pressure data reported (90 of 97), only one patient was normotensive.…”
Section: Discussionmentioning
confidence: 99%